(3agQSJs - (3eMeO GdJGhOj Hf eMeO GdWGdH Hf eMeO Hf Ydj GHf ShOg GdeQj,J (B1209 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GUWai dcJGHg ef Ndbg CaQGOkG , hLYd efge Medg dTQY Ojfg hYOI hSfGOkG s
(3BNQgG (B:s
(3hefge Gdhdi GdUGdM CHh eMeO SjOi GdMGL YHO Gddg CRhQ , QMeI Gddg JYGdi hfaYfG Hg Bejf GfJgi HMeO Gddg s
(3fSNI KGfjIs
(3HChdgG JQLeI ddJGhOi Hf ShOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B62 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B125s
(3Odjd eDQN GdeZQH (B- (3U (B359 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B316 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs